Pengaruh Perilaku Kerja Inovatif terhadap Kinerja Pegawai pada Dinas Kependudukan dan Catatan Sipil Kota Gorontalo - Riri Reftiani Tico; Yulianti Adam; Adeliana Amiruddin; Ariawan Ariawan (Journal of Technopreneurship on Economics and Business Review, 2023)
This study aims to investigate whether or not innovative work behaviors (X) covering idea exploration (X1), idea generation (X2), idea championing (X3), and idea implementation (X4) have a positive effect simultaneously or partially on employee performance (Y) at the Civil Registry Service Office of Gorontalo City. The data collection is through a list of questions tested in two stages, namely validity and reliability tests for each item contained in the list of questions. The analytical method used is path analysis. The results of the study show that innovative work behaviors (X) covering idea exploration (X1), idea generation (X2), idea championing (X3), and Idea Implementation (X4) have a positive effect simultaneously or partially on performance (Y). The Idea Exploration (X1) partially has a positive and significant effect on the employee's performance. The Idea Generation (X2) partially has a positive and significant effect on employee performance. The idea championing (X3) partially had a positive and significant effect on employee performance. The idea of implementation (X4) partially has an insignificant positive effect on employee performance.